Environmental triggers of hospital admissions for school-age children with asthma in two British cities. Issue 10 (4th October 2012) - Julious, Steven A; Jain, Ritika; Mason, Suzanne
Abstract : Research has reported seasonal peaks in asthma in school age asthmatic children. The study aimed to assess if hospital admissions could be predicted from the possible environmental triggers using data from two British cities: Aberdeen and Doncaster. However, there were no consistent patterns across the two cities with no clear evidence that hospital admissions could be predicted from environmental data.